Get detailed and accurate responses to your questions with IDNLearn.com. Get accurate answers to your questions from our community of experts who are always ready to provide timely and relevant solutions.

2x-1-(-x+3) = 6-2x SHOW STEPS....DUE TODAY

Sagot :

Answer:

x=2

Step-by-step explanation:

Simplify both sides of the equation.

2x−1−(−x + 3)=6−2x

(Distribute the Negative Sign)

2x−1 + −1(−x + 3)=6−2x

2x + −1 + −1(−x) + (−1)(3)=6−2x

2x + −1 + x + −3=6−2x

2x + −1 + x + −3=6 + −2x

(Combine Like Terms)

(2x + x) + (−1 + −3)=−2x+6

3x + −4=−2x + 6

3x−4=−2x + 6

Add 2x to both sides.

3x−4 + 2x=−2x + 6 + 2x

5x−4=6

Add 4 to both sides.

5x−4 + 4=6 + 4

5x=10

Divide both sides by 5.

5x/5=10/5

x=2